Meiotic behaviour and B chromosomes in Argentine populations of chrysolaena verbascifolia (vernonieae: asteraceae) - Via Do Pico, Gisela Mariel (2017)
Fil: Via Do Pico, Gisela Mariel. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.